PEMBENTUKAN KARAKTER ISLAMI MELALUI PEMBIASAAN DZIKIR SORE DAN KETELADANAN GURU DI SATIT PHATNAWITYA DEMONSTRATION SCHOOL, YALA - Fiqih Ahmad Alfisyahri; Rizka Harfiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze in depth the role of the habit of afternoon dhikr (recitation of God) and teacher role models in developing students' Islamic character at Satit Phatnawitya Demonstration School, Yala, Southern Thailand. This research is motivated by the importance of strengthening Islamic character education amidst the challenges of globalization, particularly in the context of Islamic schools located in Muslim-minority areas. This study uses a descriptive method combined with a qualitative approach. Data collection included analysis of school religious program documentation, interviews with Islamic Education teachers, dhikr activity instructors, and students, and direct observation of the afternoon dhikr program. Using triangulation of sources and methods to ensure data accuracy, data analysis was conducted thematically through data reduction, data presentation, and conclusion formulation. The results of this study indicate that the development of students' Islamic character is significantly facilitated by the regular, systematic, and consistent practice of afternoon dhikr, which is encouraged by teacher role models. These values ​​include religiousness, self-control, emotional calm, sincerity, patience, and responsibility. Besides being a religious practice, dhikr is a spiritual teaching tool that helps improve students' psychological stability, emotional regulation, and self-awareness.